Hukum Dan Konsumen Anak(Studi Perlindungan Hukum Terhadap Penayangan Reality Show Di Televisi) - Sukempi, Mendes; , Dr. Kelik Wardiono, S.H., M.H (2017)
ABSTRACT Television programs that many developing nowadays, namely infotainment, variety shows, soap opera, quiz and reality show that is popular now. Several establishment of community characteristics arebased on the television programs which they watch. The producer television have to think whatthe television programandwho watch the show, not only think aboutthe existence of a reality show on the television. In particular, children are as a consumer watching a reality Show and the children protection becomes one of the tools to achieve compliance with the Declaration of Rights of Children in the 10thprinciple. The government should take a part in protecting the rights of children as the nation's future, though indirectly. The protection of the children can also be used as a solution barring broadcasts on television reality show. keywords : reality show, consumer, protection of children